Learning Strategies and Learner Preferences - Khadka, Krishna Kumari (Rupantaran: A Multidisciplinary Journal, 2020)
Learning and teaching is a difficult job. Moreover, there are different ways of learning for all students. This article highlights how different learners learn in a different way, i.e. what different strategies they use in learning. All learners are different. And, this is more specifically based up on the students in that they have their own individual techniques in learning. We have rarely been able to address the individual variations in a class. Building on a survey study, this article emphasizes the fact that the techniques and learning strategies of the learners be addressed. For the purpose of the study, 50 students from a school of Lalitpur District were purposively selected and inquired via a questionnaire regarding the strategies they more preferred. They were form the secondary level. The article concludes that like other level learners, they also have various ways of doing the things during learning and this is to be understood by every teacher.